Identifikasi Jenis Siput (Gastropoda) Di Perairan Moudolung, Kabupaten Sumba Timur: Identification of Gastropod Species in the Waters of Moudolung, East Sumba Regency - Ndahawali, Suryaningsih; Tega, Yatris Rambu (Program Studi Budidaya Perairan Universitas Mataram, 2025)
The intertidal zone is an area that has a narrow area because it borders land and is influenced by tides. The types of biota in tidal areas have high diversity. There are many types of biota such as fish, bivalves, coral reefs, gastroda and there are also types of plants such as macroalgae, seagrass and mangroves. One of the biota found in tidal areas is Gastropods from the phylum mollusca which has quite abundant species diversity. With location conditions such as sandy, muddy and rocky substrates. Moudong waters are waters that have rocky and muddy topography, so they are a place/habitat for gastropod species. The aim of this research was to see the level of diversity of gastropod types and nutritional content. The method used is the observation and line transect method, with 9 stations and 9 plots on each transect. Based on the results of research on the types of gastropods in Moudong waters, there are 5 types of gastropods, namely Oliva fordi, Telescopium Telescopium, Steromphala umbilicalis, Canarium labiatum, Familia muricidae. The level of diversity of gastropod species is low with an H' index < 2.0, because there is only 1 type at each sampling station. For nutritional content (proximate analysis results), it was found that the nutritional content of the gastropod species obtained in Moudolung waters was quite high, one of which was that the protein content of each type was quite high.